2000
DOI: 10.1097/00002060-200007000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Post-Stroke Spasticity Management with Repeated Botulinum Toxin Injections in the Upper Limb

Abstract: This investigation is relevant clinically because repeated BTX-A injections show unchanging effectiveness in the management of focal spasticity after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 21 publications
2
51
0
2
Order By: Relevance
“…51 Six uncontrolled studies have examined the effects of repeated injections. [57][58][59][60][61][62] These studies are summarised in Appendix 1, Table 36. Repeat injections decreased muscle tone by a similar amount after each injection and improved passive functional scores by a similar amount to the initial injection.…”
Section: Review Of the Evidence For Treating Upper Limb Spasticity Dumentioning
confidence: 99%
See 1 more Smart Citation
“…51 Six uncontrolled studies have examined the effects of repeated injections. [57][58][59][60][61][62] These studies are summarised in Appendix 1, Table 36. Repeat injections decreased muscle tone by a similar amount after each injection and improved passive functional scores by a similar amount to the initial injection.…”
Section: Review Of the Evidence For Treating Upper Limb Spasticity Dumentioning
confidence: 99%
“…Repeat injections decreased muscle tone by a similar amount after each injection and improved passive functional scores by a similar amount to the initial injection. [58][59][60]62 Two studies measured active function 58,61 and one found improvement.…”
Section: Review Of the Evidence For Treating Upper Limb Spasticity Dumentioning
confidence: 99%
“…1 Recent studies have reported that muscular injections of botulinum toxin type A decreases muscular tone in hypertonic muscles of the hand, with improvement in the use of the upper limb and a decrease in complications. [2][3][4][5] However, in a small number of patients, the development of neutralizing antibodies can reduce the efficacy of treatment. In addition, the dosage of botulinum is not always sufficient to treat extensive and severe hypertonia in upper and lower limbs.…”
mentioning
confidence: 99%
“…However, unlike botulinum toxin, no obvious weakness in the target muscle [34]. Chronic spasticity itself would further worsen joint resistance through fibrosis of inactive connective tissue due to structural and mechanical changes in the muscle [35]. So, reducing the stiffening of connective tissue caused by fibrosis of chronic hypertonic muscles would diminish spasticity [11].…”
Section: Methodsmentioning
confidence: 99%
“…Different treatment methods have been used for treatment of spasticity include physical therapy, oral anti-spastic drugs, chemical nerve block and motor point block using phenol or ethyl alcohol and botulinum toxin injection [5,6]. It has been reported that muscular injections of botulinum toxin type A decreases muscular tone in hypertonic muscles of the hand, with improvement in the use of the upper limb and a decrease in complications [7][8][9][10]. However, the development of neutralizing antibodies can reduce the efficacy of treatment.…”
mentioning
confidence: 99%